The Polish Variant of Patriarchy? Explaining the Relationship Between Gender Inequality and Violence Against Women in Poland - Grzyb, Magdalena (Violence against women, 2024)
The largest European victimization survey of violence against women (VAW), has revealed an interesting paradox: countries with the highest gender equality indices had the highest VAW indices, while countries with low gender equality, also had low VAW indices. The country with the lowest VAW rates was Poland. This article attempts to explain this paradox. First, the results of the FRA study regarding Poland and its methodological issues are described. As these explanations may prove insufficient, it is necessary to recourse to sociological theories of VAW, together with analyses of the sociocultural roles of women, and gender relations since the communist period (1945–1989). The key question is whether the Polish variant of the patriarchy is more respectful toward women than Western European gender equality.